Buddhist Culture of Contemporary West Bengal (Reflections on the Bengali-speaking Buddhists) - Rup Kumar Barman (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2022)
Since the inception of Buddhism, the people of Bengal have maintained a very close relationship with Buddhist ideologies. In fact, Bengal appeared as a dominant center of Buddhist culture in the early medieval period (sixth to twelfth century CE) both for its institutional flavour as well as for state- sponsorship. However, with the fall of royal patronage and the conversion of the Buddhists to other religious faiths, Buddhism gradually lost its prominence in Bengal. It was during the colonial period (1757 to 1947 CE), Buddhism again started reviving in different corners of Bengal principally in the early twentieth century. However, the ‘Partition of Bengal Province (in 1947) appeared as a serious setback for the fate of Buddhism in this region. The East Bengali Buddhists had started a new episode of the struggle for survival in India more precisely in West Bengal as ‘refugees’ or as ‘asylum seekers. After their migration to West Bengal, the Bengali-speaking Buddhists have aspired to build up several Viharas (monasteries), Sanghasrams (spiritual hermitage), temples, and institutions in Kolkata, Sub-Himalayan Bengal, and certain other districts of West Bengal. They have preserved and maintained the Buddhist socio-cultural traditions that they have inherited from the southeastern corner of former East Bengal. This paper highlights all these aspects of the Buddhist culture of West Bengal with a fresh outlook.